Structural Semiotics of the Debt Verse: Foundations of Financial Ethics and Character Education in the Digital Era - Wiwik Prasetiyo Ningsih (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2025)
Ayat Dain (QS. Al-Baqarah: 282) is the longest verse in the Qur’an, emphasizing fundamental principles of financial transactions such as honesty, transparency, justice, and responsibility. In the digital era, financial practices have become increasingly complex, raising the problem of how these ethical values can serve as a foundation for digital financial management and character education. This study specifically addresses the problem of how the linguistic structure and semiotic signs of Ayat Dain can be interpreted through Ferdinand de Saussure’s structural semiotics approach and how these interpretations may contribute to character education in the digital age. The main objective of this research is to analyze the semiotic structure of Ayat Dain in order to uncover its deeper meaning related to financial ethics and to formulate a character education model grounded in these values. The research employs a qualitative method with data obtained through literature studies on classical and contemporary Qur’anic interpretations, further analyzed using Saussurean linguistic concepts to explore signifier-signified relations within the verse. The results indicate that the semiotic analysis of Ayat Dain reveals a coherent structure underscoring the necessity of transaction documentation, the inclusion of witnesses as an element of transparency, and the reinforcement of trust as the basis of financial credibility. The study contributes by proposing the integration of these ethical financial values into character education through Islamic financial literacy, the application of digital transaction recording tools, and embedding ethical financial principles within Islamic economics curricula. This integration highlights the enduring relevance of Ayat Dain in guiding ethical practices for financial and character development in the digital era